House & Atelier for Luis Barragán and San Cristobal : (arch. Andrés Casillas, Collaborator) - Ambasz, Emilio
Sobre la obra del arquitecto.
Keywords: BARRAGAN, LUIS; TRAYECTORIA PROFESIONAL; ARQUITECTOS